Imaging of cystic fibrosis lung disease and clinical interpretation = Bildgebung der Lunge bei Mukoviszidose und klinische Interpretation - Wielpütz, Mark Oliver; Eichinger, Michael; Biederer, Jürgen; Wege, Sabine; Stahl, Mirjam; Sommerburg, Olaf; Mall, Marcus A.; Kauczor, Hans-Ulrich; Puderbach, Michael (RöFo, 2016)
Progressive lung disease in cystic fibrosis (CF) is the life-limiting factor of this autosomal recessive genetic disorder. Increasing implementation of CF newborn screening allows for a diagnosis even in pre-symptomatic stages. Improvements in therapy have led to a significant improvement in survival, the majority now being of adult age. Imaging provides detailed information on the regional distribution of CF lung disease, hence longitudinal imaging is recommended for disease monitoring in the clinical routine. Chest X-ray (CXR), computed tomography (CT) and magnetic resonance imaging (MRI) are now available as routine modalities, each with individual strengths and drawbacks, which need to be considered when choosing the optimal modality adapted to the clinical situation of the patient. CT stands out with the highest morphological detail and has often been a substitute for CXR for regular severity monitoring at specialized centers. Multidetector CT data can be post-processed with dedicated software for a detailed measurement of airway dimensions and bronchiectasis and potentially a more objective and precise grading of disease severity. However, changing to CT was inseparably accompanied by an increase in radiation exposure of CF patients, a young population with high sensitivity to ionizing radiation and lifetime accumulation of dose. MRI as a cross-sectional imaging modality free of ionizing radiation can depict morphological hallmarks of CF lung disease at lower spatial resolution but excels with comprehensive functional lung imaging, with time-resolved perfusion imaging currently being most valuable. Key Points: Hallmarks are bronchiectasis, mucus plugging, air trapping, perfusion abnormalities, and emphysema. Imaging is more sensitive to disease progression than lung function testing. CT provides the highest morphological detail but is associated with radiation exposure. MRI shows comparable sensitivity for morphology but excels with additional functional information. MRI sensitively depicts reversible abnormalities such as mucus plugging and perfusion abnormalities.
Gesehen am 05.01.2018